Pemerataan Pembangunan Infrastruktur Lahan Parkir di Universitas Pembangunan Nasional “Veteran” Jakarta Menurut Mahasiswa Fakultas Hukum UPNVJ 2020-2022 - Khairunnisa, Nasywa; Liztha Maharani, Nabilah; Rifky Trihandoko, Ronaldindo; Syihab, M. Alvin; Andreas Ramadhani, Renald; Naufal Nabil, Tamam; Zybila, Agista; Maretia Lidowati, Alvina; Zaki, Akmal; Triadi, Irwan; Satino, Satino; Khoiril Anam, Ahmad; Irawan, Irawan (Peneliti.net, 2024)
This research aims to be carried out to identify how parking lots are distributed and what the views of the 2020-2022 law faculty students at Jakarta Veteran Development University are regarding the equitable development of parking lot infrastructure at Jakarta Veteran Development University. This research uses a qualitative approach using in-depth interviews with a group of law students from the 2020-2022 class. Data was analyzed thematically to identify various student complaints regarding parking problems at the Jakarta Veteran Development State University. The results of the research show that the Jakarta Veteran Development University has made efforts to equalize the development of available parking infrastructure, as well as implementing technology for more efficient parking management. However, students as parking lot users report the need for expansion and improvement in accessibility and comfort for all students.